Systém odměňování a benefitů ve společnosti XY - Libišová, Hana; Hana Libišová (České vysoké učení technické v Praze, 2019)
Obsahem této bakalářské práce je popsání, analyzování a zhodnocení funkčnosti za-vedeného systému odměňování a zaměstnaneckých benefitů ve společnosti XY. Práce je rozdělena do dvou částí, teoretickou část a část praktickou. V teoretické části jsou definovány pojmy související s odměňováním a zaměstnaneckými benefity. V praktické části je představena analyzovaná společnost XY a analýza této společnosti. Informace nacházející se v praktické části jsou poskytnuté společností XY. Závěr pak obsahuje návrh doporučení možných změn v těchto systémech.

The content of the bachelor thesis is the description, analysing and evaluation of func-tionality of remuneration system and employee benefits in company XY. The thesis consists of two parts, part theoretical and part practical. The theoretical part defines terms related to remuneration and employee benefits. In the practical part there is introduced the analysed company XY and the analysis of this company. The information in the practical part is provided by XY. The conclusion includes proposal of recommendations for possible changes in these systems.
The System of Remuneration and Benefits in Company XY
Keywords: Odměňování zaměstnanců; systém odměňování; typologie odměňování; motivace; zaměstnanecké benefity; Remuneration of employees; remuneration system; typology of wages; motivation; employee benefits